Quality of Crispy Seasoned Flour with Tumang Sago Substitution (Mexroxylon sago Rottb) as a Substitute for Wheat Flour and its Application in Broilers (Jurnal Ilmu dan Teknologi Hasil Ternak, 2022)
The utilization of local resources such as tumang sago flour is needed to be conducted to increase diversification of local food with superior quality. This study aims to determine the physicochemical and functional quality of crispy seasoned flour using tumang sago substitution. In addition, the sensory quality of the chicken crispy is also checked using those spiced flour. Tumang sago flour was obtained by drying the sago under the sun until it was dry and then sifted using a 100 mesh sieve. This study used a total of 5 treatments with 5 times. Four treatments were applied namely control (without substitution of sago tumang flour); 10%; 20%; 30% and 40% of sago tumang flour. Observations were made on the crispy seasoning flour, among others: Water Content (SNI-01-02891-1992); Crude Fiber Content (Sudarmadji, et al. (1997); Water Holding Capacity (Subagio, 2006); Oil Holding Capacity (Subagio, 2006); Color (L, a and b) (Digital Colorimeter), while the sensory test chicken crispy (color, aroma, crunch, taste and acceptability). Data on physicochemical quality and color using a digital colorimeter were analyzed using a completely randomized design with a unidirectional pattern, while the quality of crispy chicken accessories was analyzed by Kruskall Wallis' Non-Parametric analysis. If there is a real effect, then Duncan's test is continued. The results showed that the quality of seasoning flour is moisture content (12.518-15.208%), crude fiber content (0.396-2.138%), WHC (64.606-89.855%), OHC (96,373-115,498%), L (87.677-93.330), a (2,153-2,697), b (5,630 – 7,743), while the sensory quality of crispy chicken is color (1,57-4,29), aroma (2,00-4,14), crispy (3,57-3,86), taste (2,86-3,86) and receptivity (2,57-4.00). The addition of Tumang sago flour in different percentages had a significant effect (P<0.05) on water content, crude fiber content, WHC, OHC, color (digital colorimeter), color sensory parameters, scent and acceptance of crispy chicken. In conclusion, the best treatment in this study was seasoned flour with the addition of 10% sago flour.